Simulation and thermodynamic evaluation of steam cogeneration system configurations for energy recovery from exhaust gases of a carbo-chemical industry - Quintão, Alexsander Luiz; Sant’ana, Brunella Bermudes Prati; Fonseca, Francisco Mello; de Faria, Pedro Rosseto; Santos, José Joaquim Conceição Soares (Frontiers in Chemical Engineering, 2025)
Energy efficiency is a critical factor in the transition toward sustainable energy systems and the decarbonization of industrial processes. In this context, the recovery of residual process energy represents a key strategy. This study presents a case analysis of a Brazilian carbo-chemical plant, where calcination furnaces release exhaust gases containing both thermal and chemical energy. These gases, generated by six furnaces, have a total flow rate of 1.36 kg/s at 800 °C and a volumetric composition of 26% H2, 4.2% CH4, and 5% CO, among other components, resulting in a total energy potential of 8.30 MW—comprising 1.63 MW of thermal and 6.67 MW of chemical energy. The main objective of this study is to assess the potential for recovering this energy through various cogeneration system configurations based on steam cycles, aimed at process thermal oil heating and electricity generation. Simulations were conducted using IPSEpro 8.0, and system performance was evaluated according to the First and Second Laws of Thermodynamics to identify opportunities for optimization. The results show that, in addition to providing 70 kW of useful heat for oil heating, the system can deliver up to 2.65 MW of electrical power. The energy and exergy efficiencies of the steam cycles reach 43.35% and 80.45%, respectively, while the overall system achieves energy and exergy efficiencies of 32.8% and 32.03%. Exergy analysis highlights areas for improvement, particularly in combustion and heat exchange, due to high irreversibilities in combustion chambers and boilers (up to 821.50 kW and 3384.29 kW, respectively) and recoverable heat present in boiler exhaust gases. Environmental analysis indicates a significant reduction in stack gas temperatures (66%–77% relative to the initial 800 °C) and the combustion of residual fuel components, especially CH4, which markedly decreases thermal and chemical pollution. Quantitatively, electricity generation reduces grid dependency, preventing up to 3234 tons of CO2 emissions per year. These findings demonstrate a considerable theoretical estimable potential for residual energy recovery, yielding substantial improvements in efficiency and environmental impact mitigation. Furthermore, an optimized technological approach could achieve energy efficiencies of up to 50%, producing 40% more electricity. These results highlight the importance of further studies, particularly to evaluate economic feasibility and potential integration into carbon markets.